Bhekizizwe Peterson’s Black Love project - Kiguwa, Peace (PINS-Psychology in Society, 2024)
Bhekizizwe (Bheki) Peterson was an African literary scholar, filmmaker, artist, and community activist. While all accurate descriptors, to describe him thus leaves absent his underlying project of Black Love. It is love that is present in his project of recovery of Black intellectual and cultural legacies; in his teaching and mentorship marked by intergenerational dialoguing in a joint quest for freedom; and it is love in his injunction to challenge our rigid disciplinary imaginations of interior lives and social imaginaries that attend to the “continuities and discontinuities between past, present and future” (Peterson, 2019b, p. 345). In this paper, I think with Bheki on 1) the act of writing; 2) African ontology’s relevance for trauma and healing and 3) the moral template of personhood as part of his ‘buzzing’ against disciplinary imaginaries. This paper is an invitation to re-imagine disciplinary boundaries by orientating psychology to the scholarship of Bhekizizwe Peterson, and to take up his questions on the narratable subject and complexities of personhood. I consider Bheki’s reflection on the act of writing and implications of narratable subjects that are part of a moral economy of what it means to be human.